EFEKTIVITAS PENGGUNAAAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN TERHADAP PROSES BELAJAR SISWA DIBANDINGKAN DENGAN METODE KONVENSIONAL DI SMPN 6 KARAWANG BARAT - Zuraida Aprilia; Adinda Rahmasari; Ahmad Naufal Fajri; Renhar (JURNAL ILMIAH NUSANTARA, 2025)
. This study aims to analyze the effectiveness of the use of digital technology in the learning process on student achievement at SMPN 6 Karawang Barat, compared to conventional learning methods. The background of this study is based on the needs of the world of education to adapt to technological developments and the challenges in improving student learning outcomes in the digital era. This study uses a quantitative approach with a quasi-experimental design. The subjects of the study consisted of two groups of students: an experimental group that followed digital technology-based learning, and a control group that used conventional methods. The main instrument in this study was a learning achievement test given before and after treatment (pretest and posttest). The results of the data analysis showed that there was a significant difference between the learning achievements of students who used digital technology and students who followed conventional methods. Students in the experimental group showed a higher increase in learning outcomes. These findings indicate that the use of digital technology in learning is more effective in improving student achievement compared to traditional methods. This study recommends continuous integration of technology in the teaching and learning process in schools as an effort to improve the quality of education.